2020
DOI: 10.1159/000507351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Androgen Deprivation Therapy on Non-Alcoholic Fatty Liver Disease in Patients with Prostate Cancer: A CT Evaluation

Abstract: Purpose: The aim of this study was to investigate the influence of androgen deprivation therapy (ADT) on the progression of non-alcoholic fatty liver disease (NAFLD) in patients with prostate cancer (PCa) by evaluation of hepatic steatosis on computed tomography (CT). Methods: The study included 77 PCa patients who underwent abdominal CT at baseline and after 6 months of ADT. The degree of hepatic steatosis was evaluated according to the attenuation value for liver parenchyma (CT LP ), the attenuation ratio fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…A dose–response relationship was noted between the number of androgen deprivation therapy doses and NAFLD 44 . Another study showed that 6 months of androgen deprivation therapy was associated with significant progression in NAFLD in patients with prostate cancer 45 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A dose–response relationship was noted between the number of androgen deprivation therapy doses and NAFLD 44 . Another study showed that 6 months of androgen deprivation therapy was associated with significant progression in NAFLD in patients with prostate cancer 45 …”
Section: Discussionmentioning
confidence: 97%
“…44 Another study showed that 6 months of androgen deprivation therapy was associated with significant progression in NAFLD in patients with prostate cancer. 45 TA B L E 4 Multivariable odds ratios of risk factors for NAFLD using Hepatic Steatosis Index according to sex hormone levels in postmenopausal women (n = 2209). TA B L E 5 Multivariable odds ratios of risk factors for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the prostate gland and liver have developed earlier than other primary sites of cancer (Gild et al., 2018). At present, there are six studies that evaluated the relationship between NAFLD and PCa (Allen et al., 2019; Arase et al., 2012; Choi et al., 2014, 2018; Kim et al., 2017; Sawazaki et al., 2020). A study conducted in Japan indicated that the prevalence of PCa in the NAFLD Japanese population was recorded at 1.3 per cent (Arase et al., 2012), but this study did not provide the prevalence of PCa in those without NAFLD.…”
Section: Nafld and Prostatic Diseasesmentioning
confidence: 99%
“…(2019) observed that NAFLD was significantly correlated with a high risk of PCa after adjusting for age (HR = 1.8, 95% CI: 1.2–2.7). Besides, Sawazaki et al demonstrated that six months of androgen deprivation therapy was related to the remarkable progression of NAFLD in PCa patients (Sawazaki et al., 2020).…”
Section: Nafld and Prostatic Diseasesmentioning
confidence: 99%
“…Epidemiological studies demonstrated that the diagnosis of NAFLD and even cirrhosis was more common after ADT in patients without known liver disease at baseline, with an apparent dose-response relationship [69]. In addition, in patients with diagnosed NAFLD, 6 months of ADT was associated with the progression of hepatic steatosis on abdominal CT [70].…”
Section: Sex Hormones Hormonal Therapy and Nafld: Evidence From Clinical Practicementioning
confidence: 99%